THE APPLICATION OF TRANSCULTURAL NURSING MODEL IN PERSPECTIVE OF MADURA CULTURE IMPROVING BREASTFEEDING MOTHER’S BEHAVIOR IN JEMBER - Awatiful Azza; Cipto Susilo (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Background and objective : Breastfeeding is one of the development tasks for women after childbirth. Many factors can affect mother’s success in breastfeeding exclusively, such as family support as well as local cultural influences. This research aims to apply the transcultural nursing model in Madura cultural perspective in breastfeeding mothers.Method: This research was conducted in Public Health Centre of Pakusari Suboh Jember. The data were collected using questionnaires, and focus group discuss. The research design was question-experimental research of post test design with control by using Paired Samples Test analysis. In addition, the researchers also performed a qualitative analysis to explore the Maduranese culture. The samples were breastfeeding mothers who had infants aged 1-6 months and 50 samples were then divided into two, i.e., treatment and control groups. Also, another data source were health professionals.Result: The result showed that the maternal age range between 15-34 years with an average age of 27 years. Besides, the average of the respondents’ education background was that 60% of them did not pass elementary school, both in treatment group and control group. The results of the analysis on cultural modifications was p-value of 0.001, which means that there is the effects of applying transcultural nursing model in improving milk production.Conclusion and recomendation : An application of cultural modifications that is able to increase milk production. Therefore, it needs a good cooperation for all the components of society in supporting breastfeeding mothers by modifying less the local culture that becomes  favorable for health.